Design of Gas Leakage Monitoring System Based on Android Application and NodeMCU ESP8266 - Nabil Fuadi; Fauzi, Achmad; Khair, Husnul (Yayasan Kita Menulis, 2024)
Gas leakage is a serious problem that can threaten public safety and health and cause significant material losses. This research aims to design and implement a gas leak monitoring system that can be accessed remotely based on Android applications and NodeMCU ESP8266. NodeMCU ESP8266 is chosen as the main microcontroller equipped with an MQ-2 gas sensor to detect the presence of hazardous gas. This research incorporates Internet of Things (IoT) technology to allow users to remotely monitor the condition of gas leaks, thereby increasing the level of safety in the use of gas in households or small industries. The hardware design includes the use of an MQ-2 gas sensor that is sensitive to certain gas concentrations, as well as setting up an ESP8266 NodeMCU to transmit detection data to a Firebase server for later access through an Android application. The Android application was developed using Android Studio with a focus on an intuitive user interface to monitor the status of gas leaks in real-time. he research methods used include system design, hardware and software implementation, and thorough system testing by simulating gas leak scenarios to test the reliability and response of the system. The results show that the system can detect gas leaks with high accuracy. It is expected that the system developed in this research can be a practical and effective solution in reducing the risk of accidents caused by gas leaks, as well as making a positive contribution in increasing awareness of the safety of gas use in the community.